The effect of oil palm empty fruit bunch (Elaeis guineensis Jacq.) fiber addition at various volume fractions on the compressive strength of flowable composite resin - Heikal Faried Abdullah; Rahmi Khairani Aulia; Aria Fransiska (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Oil palm empty fruit bunch (OPEFB) fibers have emerged as a promising natural alternative to synthetic fibers due to their mechanical strength and biocompatibility, although research on their use as a reinforcing in composite resin remains limited. This study aimed to evaluate the effect of OPEFB fiber incorporation on the compressive strength of flowable composite resin. A true experimental design with a post-test-only control group was employed. The OPEFB fibers underwent chemical and double silane treatments and were randomly oriented prior to incorporation. Fifteen cylindrical specimens (6 mm × 12 mm) were allocated into three groups based on fiber volume fraction (0%, 1%, and 1.5%). Compressive strength was tested using a universal testing machine following ASTM D-695 standards. Data were analyzed using one-way ANOVA (p < 0.05) followed by a post-hoc Least Significant Difference (LSD) test. The mean compressive strength of flowable composite resins at 0%, 1%, and 1.5% OPEFB fiber volume fractions were 261.99 ± 17.64, 301.20 ± 19.26, 368.52 ± 14.90 MPa. One-way ANOVA test showed that the mean compressive strength in the three groups was significantly different (p < 0.05). The post-hoc LSD test showed significant differences (p < 0.05) among all groups. This study concluded that the incorporation of OPEFB fiber can enhance the compressive strength of flowable composite resin, with the highest reinforcement observed at the 1.5% OPEFB fiber volume fraction.